Buying to Sell: Private Equity Buyouts and Industrial Restructuring - Pehr-Johan Norbäck; Lars Persson; Joacim Tåg (Center for Economic Studies and ifo Institute (CESifo), 2013)
We show how temporary ownership by private equity firms affects industry structure, competition and welfare. Temporary ownership leads to strong investment incentives because equilibrium resale prices are determined by buyers incentives to block rivals from obtaining assets. These incentives benefit consumers, but harm rivals in the industry. Evaluating optimal antitrust policy, we underscore that an active private equity market can aid antitrust authorities by triggering welfare-enhancing mergers and by preventing concentration in the industry. By spreading the cost of specializing in restructuring over multiple markets, private equity firms have stronger incentives than incumbents to invest in acquiring specialized restructuring skills.
Keywords: G32; G34; L13; L22; L40; 330; antitrust; competition policy; leveraged buyouts; mergers and acquisitions; private equity; temporary ownership